Autonomy-Based Reasons for Limitarianism - Zwarthoed, Danielle (Ethical theory and moral practice, 2018)
This paper aims to provide autonomy-based reasons in favour of limitarianism. Limitarianism affirms it is of primary moral importance that no one gets too much. The paper challenges the standard assumption that having more material resources always increases autonomy. It expounds five mechanisms through which having too much material wealth might undermine autonomy. If these hypotheses are true, a theory of justice guided by a concern for autonomy will support a limitarian distribution of wealth. Finally, the paper discusses two issues autonomy-based limitarianism would raise. First, insofar as coercion invades autonomy, do autonomy-based reasons legitimate coercive measures to secure a limitarian distribution of wealth? Second, is a limitarian ethos consistent with the incentive to produce enough wealth to secure distributive justice?